Approaching Negotiation at the Organizational Level. (6th October 2017) - Borbély, Adrian; Caputo, Andrea
Abstract: How can an organization improve its negotiation skills? The following article aims to answer this question by investigating how, and why, an organization's negotiation capability should be developed. We propose a four‐level Organizational Model of Negotiation (OMoN), in which the individual level (I) concerns how people interact at the negotiation table; the linkages level (II) concerns how different negotiations impact one another; the infrastructure level (III) concerns how an organization may organize its negotiation functions; and finally, the capability level (IV) concerns how negotiation can be the source of competitive advantage. Our framework opens the path for developing the understanding of this issue by presenting teaching resources and identifying a possible theoretical underpinning. The article also presents a broad research agenda, which offers the basis for future studies to integrate concepts from different fields of research, such as from the management and strategy literature, into the field of negotiation.